Pengaruh Case Based Learning menggunakan Cisco Packet Tracer Terhadap Kemampuan Berpikir Kreatif Siswa Kelas XI di SMAK Untung Suropati Krian - Hylda Gusti Ina Simanjuntak; , Bachtiar Syaiful Bachri; Irene Yolanita Maureen (LP. Ma'arif Janggan Magetan, 2024)
This research aims to determine the influence of Case-Based Learning (CBL) method using Cisco Packet Tracer on the creative thinking ability of students. The type of research carried out was quantitative using a Quasi-experimental method, with a nonequivalent pretest posttest group design model, 62 research subjects divided into experimental and control groups. The instrument used is a test sheet with indicators to measure creative thinking ability. Data were collected twice through pre-test and post-test. Processing and data analysis using Independent Sample T-Tes. The results showed that both data were statistically normally distributed, the data were statistically homogeneous, and the results of the hypothesis testing of both data showed a significant effect. The conclusion informs that there is an effect of case-base learning using cisco packet tracer on students’ creative thinking ability in grade eleven of SMAK Untung Suropati Krian.